Female labor force participation and gross domestic product in the Peninsular Malaysia using Panel Cointegration and Granger Causality testing / Siti Sarah Januri ... [et al.] - Januri, Siti Sarah; Md Yasin, Zaitul Anna Melisa; Ahamad, Mas Hamizah; Roseli, Rosmini; Mohd Ridza, Mohamad Saifuddin; Azmi, Sharina Salmi (Universiti Teknologi MARA, Perak, 2021)
Malaysia’s economy has experienced significant structural changes from being an agricultural-based economy to a manufacturing-dominated one. The economic growth nevertheless has also increased the cost of living and noted a repercussion to the number of married couples due to the women nowadays are focused on their career. This study investigates the relationship between the female labour force participation (FLFP) and gross domestic product (GDP) for thirteen states in Malaysia. The results of the study indicated that both variables were stationary after the first differencing. The seven Pedroni test statistics obtained from the co-integration test indicated the significance of the variables hence the conclusion that FLFP and GDP are co-integrated and can be treated as the dependent variables. The panel granger causality test revealed the lack of a causal relationship between FLFP and GDP, thus suggesting that FLFP has no effect in increasing GDP growth in Malaysia. Consequently, FLFP causes good relationship between children and mother.